2013
DOI: 10.4103/0974-7796.120303
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a 6 Fr catheter on flow rate in men

Abstract: Background:The pressure-flow study (PFS) is considered the gold standard for the detection of bladder outlet obstruction (BOO) in men. However, several studies have raised the possibility that transurethral catheterization might have an obstructive effect on PFS while others did not.Objectives:To evaluate the effect of a 6 Fr transurethral catheter on the pressure-flow study and to evaluate its clinical implication in men.Materials and Methods:A retrospective chart review study of 515 men referred for an evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…1 The aim of the present study was to investigate the effects of catheterization on uroflow via comparison of several urodynamic parameters during free uroflowmetry and pressure-flow study in three common aetiologies that frequently require urodynamic examination, namely benign prostatic hyperplasia, female stress incontinence, and lumbosacral spinal injury or spina bifida. [1][2][3]5 The present study showed that in patients with benign prostatic hyperplasia, Q max and Q ave were higher in free uroflowmetry than pressure-flow study, and T max had a shorter duration in free uroflowmetry versus pressure-flow study. Consistent with the present findings, a study into the effect of a 6 Fr catheter on flow rate in 133 male participants concluded that a 6 Fr transurethral catheter significantly lowered Q max by 4 ml/s.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…1 The aim of the present study was to investigate the effects of catheterization on uroflow via comparison of several urodynamic parameters during free uroflowmetry and pressure-flow study in three common aetiologies that frequently require urodynamic examination, namely benign prostatic hyperplasia, female stress incontinence, and lumbosacral spinal injury or spina bifida. [1][2][3]5 The present study showed that in patients with benign prostatic hyperplasia, Q max and Q ave were higher in free uroflowmetry than pressure-flow study, and T max had a shorter duration in free uroflowmetry versus pressure-flow study. Consistent with the present findings, a study into the effect of a 6 Fr catheter on flow rate in 133 male participants concluded that a 6 Fr transurethral catheter significantly lowered Q max by 4 ml/s.…”
Section: Discussionsupporting
confidence: 44%
“…Consistent with the present findings, a study into the effect of a 6 Fr catheter on flow rate in 133 male participants concluded that a 6 Fr transurethral catheter significantly lowered Q max by 4 ml/s. 5 According to another study however, 6 in the majority of male patients who presented with lower urinary tract symptoms secondary to benign prostatic hyperplasia, an 8 Ch (1 Ch ≈ 1 Fr) urethral catheter appeared to have no significant impact on uroflow rate. Regardless of the discrepancy in findings, the present authors believe that the effect of transurethral catheterization should be considered when analysing any results from pressure-flow study in patients with benign prostatic hyperplasia.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…V583 Δebp (ebpA to -C deletion mutant) was used as a negative control, as this strain lacks a surface pilus previously shown to be involved with the initial attachment phase in biofilm development (9), and, as expected, showed a significant decrease in biofilm formation. Drip-flow conditions were chosen to closely mimic flow rates known to be present in catheterized patients (40). We directly enumerated the CFU to get a more quantitative measure of the differences exhibited by mutation of the RRNPP homologs (Fig.…”
Section: Resultsmentioning
confidence: 99%